Phosphazene polymer / copper and phosphorus co-doped g-C3N4 heterojunction photocatalytic material as well as preparation method and application thereof

By co-doping phosphazene polymer and copper on g-C3N4 to form heterojunction photocatalytic materials, the problem of limited catalytic activity in the preparation of methane by CO2 reduction is solved, and efficient photocatalytic CO2 reduction is achieved, and the preparation process is simple and reliable.

CN119819350AActive Publication Date: 2025-04-15LINYI UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510070636.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-15
Estimated Expiration
2045-01-16

AI Technical Summary

Technical Problem

Existing photocatalytic materials such as g-C3N4 are limited in the preparation of methane when photocatalyzed CO2 reduction, have high electron hole recombination rate, insufficient visible light absorption, low specific surface area, few surface reaction activation sites, slow surface reaction kinetics, and low charge mobility.

Method used

The phosphazene polymer/copper and phosphorus co-doped g-C3N4 heterojunction photocatalytic material is used to form large and strong interfacial contact, excellent visible light absorption capacity, porous structure and spatial separation redox sites through low environmentally friendly solvents and controlled heating during the synthesis process.

Benefits of technology

The efficiency of photocatalytic reduction of CO2 to CH4 is significantly improved, and the CH4 yield can reach 1520.8 μmol g-1h-1, which is better than the catalytic activity of pure C3N4. The preparation process is simple and reliable, and it is easy to mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119819350A_ABST
    Figure CN119819350A_ABST
Patent Text Reader

Abstract

The invention discloses a phosphazene polymer / copper and phosphorus co-doped g-C3N4 heterojunction photocatalytic material as well as a preparation method and application thereof, and belongs to the technical field of CO2 reduction photocatalytic materials. The g-C3N4 is modified by codoping two elements of copper and phosphorus, and then the modified g-C3N4 is compounded with the phosphazene polymer to prepare the phosphazene polymer / copper and phosphorus codoped g-C3N4 heterojunction photocatalytic material, the material can effectively regulate and control photon-generated carrier separation, the photocatalytic activity is greatly improved, the material has ultrahigh capability of reducing CO2 into CH4, the CH4 yield can reach 1520.8 [mu] mol g <-1 > h <-1 >, and the photocatalytic activity is greatly improved. Good application prospects are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of photocatalytic CO2 reduction, and specifically relates to a phosphazene polymer / copper and phosphorus co-doped g-C3N4 heterojunction photocatalytic material and a preparation method and application thereof. Background Art

[0002] Graphitic carbon nitride (g-C3N4) is a porous carbon material composed of carbon and nitrogen with good photocatalytic performance and chemical stability. It has excellent light absorption performance and can convert light energy into chemical energy. It has applications in the fields of catalytic water decomposition, organic wastewater treatment, and photocatalytic CO2 reduction. However, g-C3N4 also has certain disadvantages, such as high electron-hole recombination rate, insufficient visible light absorption, low specific surface area, few surface reaction activation sites, slow surface reaction kinetics, and low charge mobility. These disadvantages greatly limit the photocatalytic performance of g-C3N4, especially in the photocatalytic CO2 reduction to prepare methane. So far, many photocatalytic materials such as TiO2 and Co3O4 have been used in the photocatalytic reduction of CO2, but the extremely low conversion efficiency has seriously hindered practical applications. Therefore, the search for efficient, stable, and inexpensive photocatalysts has attracted widespread attention. Summary of the invention

[0003] The purpose of the present invention is to provide a phosphazene polymer / copper and phosphorus co-doped g-C3N4 heterojunction photocatalytic material, which can better regulate the migration of photogenerated electrons and the separation of carriers, thereby improving the efficiency of photocatalytic reduction of CO2 to CH4. The preparation method is simple and feasible, low-cost, green and pollution-free, and easy to mass produce.

[0004] In order to achieve the above technical objectives, the technical solution adopted by the present invention is: A method for preparing a phosphazene polymer / copper and phosphorus co-doped g-C3N4 heterojunction photocatalytic material, comprising the following steps: (1) Melamine was calcined at high temperature for 4 h under nitrogen atmosphere to obtain g-C3N4; (2) preparing a copper salt methanol solution, slowly adding the g-C3N4 obtained in step (1) thereto while stirring, stirring and mixing evenly, heating to 65°C for reflux reaction for 3-4 h, collecting the solid precipitate after the reaction, vacuum drying it, transferring it to a tube furnace, and calcining it at high temperature for 4 h under a nitrogen atmosphere to obtain Cu-doped g-C3N4; (3) preparing a methanol solution of phosphate, slowly adding the g-C3N4 obtained in step (1) thereto while stirring, stirring and mixing evenly, heating to 65°C for reflux reaction for 3-4 h, collecting the solid precipitate after the reaction, vacuum drying it, transferring it to a tube furnace, and calcining it at high temperature for 4 h under a nitrogen atmosphere to obtain P-doped g-C3N4; (4) The Cu-doped g-C3N4 and P-doped g-C3N4 obtained in the above steps were mixed according to the mass ratio and mechanically ground for 30 min. The mixture was then placed in a nitrogen atmosphere and calcined at high temperature for 2 h. After naturally cooling to room temperature, the product was washed with methanol three times and then vacuum dried at 80 °C for 24 h to obtain copper and phosphorus co-doped g-C3N4. (5) Hexachlorocyclotriphosphazene, trithiocyanate, acetonitrile and dimethyl sulfoxide were added into a hydrothermal reactor in proportion, and ultrasonic treatment was first performed for 1 h, and then heated to 180°C and kept warm for reaction for 24-28 h. After the reaction was completed, the product was naturally cooled and washed with deionized water, acetonitrile and ethanol in sequence. After washing, the product was vacuum dried at 60°C for 24 h to obtain a phosphazene polymer; (6) The phosphazene polymer obtained in step (5) and the copper and phosphorus co-doped g-C3N4 obtained in step (4) are mixed in a mass ratio, and mechanically ground for 30 minutes to obtain the phosphazene polymer / copper and phosphorus co-doped g-C3N4 heterojunction photocatalytic material.

[0005] Preferably, the specific method of high temperature calcination in step (1) is: heating to 500° C. at a rate of 10° C. / min and then calcining for 4 hours.

[0006] Preferably, in step (2), the concentration of the copper salt methanol solution is 0.1-0.2 mol / L; the usage ratio of the copper salt methanol solution to g-C3N4 is 100 ml: 2-3 g; and the copper salt is copper chloride or copper nitrate.

[0007] Preferably, the concentration of the methanol solution of phosphate in step (3) is 0.1-0.2 mol / L; the usage ratio of the methanol solution of phosphate to g-C3N4 is 100 ml: 2-3 g; and the phosphate is sodium hypophosphite or sodium phosphite.

[0008] Preferably, the specific method of high temperature calcination in step (2) and step (3) is: heating to 520° C. at a rate of 10° C. / min and then calcining for 4 h.

[0009] Preferably, in the step (4), the mass ratio of Cu-doped g-C3N4 to P-doped g-C3N4 is 700-800:1; the specific method of high-temperature calcination is: heating to 300°C at a rate of 10°C / min and then calcining for 2 h.

[0010] Preferably, in step (5), the usage ratio of hexachlorocyclotriphosphazene, trithiocyanuric acid, acetonitrile and dimethyl sulfoxide is 1 mol: 3 mol: 25-30 L: 1.5 L.

[0011] Preferably, in step (6), the mass ratio of the phosphazene polymer to the copper and phosphorus co-doped g-C3N4 is 6-8:3.

[0012] The present invention also provides a phosphazene polymer / copper and phosphorus co-doped g-C3N4 heterojunction photocatalytic material prepared by the above method.

[0013] The present invention also provides the use of the above-mentioned phosphazene polymer / copper and phosphorus co-doped g-C3N4 heterojunction photocatalytic material in the production of CH4 by reducing CO2.

[0014] Compared with the prior art, the present invention has the following beneficial effects: (1) The heterojunction material in the present invention does not involve complicated synthesis steps. It only needs to use low-cost and environmentally friendly solvents and a controllable heating process without the need for cumbersome post-treatment processes to obtain the phosphazene polymer / copper and phosphorus co-doped g-C3N4 heterojunction photocatalytic material. The preparation process is simple and reliable and easy to mass produce.

[0015] (2) The phosphazene polymer / copper and phosphorus co-doped g-C3N4 heterojunction photocatalytic material prepared by the present invention has a super high ability to reduce CO2 to CH4, and the CH4 yield can reach 1520.8 μmol g -1 h -1 , 2.5 times higher than that of phosphazene polymer under the same conditions. This is because the heterojunction composite has large and strong interface contacts, excellent visible light absorption ability, porous structure, spatially separated redox sites, and rapid separation of photoinduced charge carriers, resulting in excellent photocatalytic performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a graph showing the XRD test results of different materials of the present invention; Figure 2 TEM image of the phosphazene polymer / copper and phosphorus co-doped g-C3N4 heterojunction photocatalytic material CT / CuPCN obtained in Example 1 of the present invention; Figure 3 This is a test diagram of the photocatalytic activity of the catalytic materials obtained in Example 1 of the present invention and the comparative example in the photocatalytic reduction of CO2 to produce methane; Figure 4 The impedance spectra of the catalyst materials of Example 1 of the present invention and the comparative example are shown. DETAILED DESCRIPTION

[0017] The technical solution of the present invention is further described below in conjunction with specific embodiments, but is not limited thereto.

[0018] Example 1 A phosphazene polymer / copper and phosphorus co-doped g-C3N4 heterojunction photocatalytic material is prepared by the following method: (1) Weigh 5 g of melamine, heat it to 500°C at a heating rate of 10°C / min under a nitrogen atmosphere, and then calcine it for 4 h to obtain g-C3N4; (2) Weigh 2.6 g CuCl2·H2O and 100 mL methanol, put them into a clean 250 mL round-bottom flask, and ultrasonicate for 1 h to prepare a uniform solution. Then, 2 g g-C3N4 was slowly added under stirring to prevent agglomeration. The mixture was refluxed at 65 °C for 3 h, cooled, and the solid precipitate was collected and dried in a vacuum oven at 70 °C for 24 h. Then, the precipitate was heated to 520 °C in a nitrogen atmosphere at a heating rate of 10 °C / min and calcined for 4 h to obtain Cu-doped g-C3N4, denoted as CuCN. (3) Weigh 1.32 g of sodium hypophosphite and 100 mL of methanol, place them in a clean 250 mL round-bottom flask, and ultrasonicate for 1 h to prepare a uniform solution. Then, slowly add 2 g of g-C3N4 under stirring to prevent agglomeration. Then, reflux the mixture at 65 °C for 3 h, cool it, collect the solid precipitate, and dry it in a vacuum oven at 70 °C for 24 h. Then, heat the precipitate to 520 °C in a nitrogen atmosphere at a heating rate of 10 °C / min and calcine it for 4 h to obtain P-doped g-C3N4, denoted as PCN. (4) 0.3 g Cu-doped g-C3N4 and 0.4 mg P-doped g-C3N4 were mixed and mechanically ground for 30 min. The mixture was then placed in a nitrogen atmosphere and heated to 300 °C at a rate of 10 °C / min and calcined for 2 h. After naturally cooling to room temperature, the product was washed with methanol three times and then dried at 80 °C in vacuum for 24 h to obtain copper and phosphorus co-doped g-C3N4, which was recorded as CuPCN. (5) Weigh 0.35 g of hexachlorocyclotriphosphazene and 0.53 g of trithiocyanate into a 50 mL hydrothermal autoclave, add 28 mL of acetonitrile and 1.5 mL of dimethyl sulfoxide, and ultrasonicate for 1 h. Seal the hydrothermal autoclave and place it in the hydrothermal autoclave. Seal the hydrothermal autoclave, and then heat the hydrothermal autoclave to 180 °C at a heating rate of 10 °C / min for 24 h. After the reaction is cooled, wash the brown precipitate with deionized water, acetonitrile, and ethanol. After washing, dry it in a vacuum oven at 60 °C for 24 h to obtain a phosphazene polymer, which is recorded as CT. (6) 0.7 mg of phosphazene polymer was mixed with 0.3 mg of copper and phosphorus co-doped g-C3N4 and mechanically ground for 30 min to obtain the phosphazene polymer / copper and phosphorus co-doped g-C3N4 heterojunction photocatalytic material, which was recorded as CT / CuPCN.

[0019] Example 2 A phosphazene polymer / copper and phosphorus co-doped g-C3N4 heterojunction photocatalytic material is prepared by the following method: (1) Weigh 5 g of melamine, heat it to 500°C at a heating rate of 10°C / min under a nitrogen atmosphere, and then calcine it for 4 h to obtain g-C3N4; (2) Weigh 4.65 g Cu(NO3)2·3H2O and 100 mL methanol, place them in a clean 250 mL round-bottom flask, and ultrasonicate for 1 h to prepare a uniform solution. Then, slowly add 3 g g-C3N4 under stirring to prevent agglomeration. Then, reflux the mixture at 65 °C for 3 h, cool it, collect the solid precipitate, and dry it in a vacuum oven at 70 °C for 24 h. Then, heat the precipitate to 520 °C in a nitrogen atmosphere at a heating rate of 10 °C / min and calcine it for 4 h to obtain Cu-doped g-C3N4, denoted as CuCN. (3) Weigh 1.32 g of sodium hypophosphite and 100 mL of methanol, place them in a clean 250 mL round-bottom flask, and ultrasonicate for 1 h to prepare a uniform solution. Then, slowly add 3 g of g-C3N4 under stirring to prevent agglomeration. Then, reflux the mixture at 65 °C for 3 h, cool it, collect the solid precipitate, and dry it in a vacuum oven at 70 °C for 24 h. Then, heat the precipitate to 520 °C in a nitrogen atmosphere at a heating rate of 10 °C / min and calcine it for 4 h to obtain P-doped g-C3N4, which is denoted as PCN. (4) 0.35 g Cu-doped g-C3N4 and 0.5 mg P-doped g-C3N4 were mixed and mechanically ground for 30 min. The mixture was then placed in a nitrogen atmosphere, heated to 300 °C at a rate of 10 °C / min and calcined for 2 h. After naturally cooling to room temperature, the product was washed three times with methanol and then dried at 80 °C in vacuum for 24 h to obtain copper and phosphorus co-doped g-C3N4, denoted as CuPCN. (5) Weigh 0.35 g of hexachlorocyclotriphosphazene and 0.53 g of trithiocyanate into a 50 mL hydrothermal autoclave, add 28 mL of acetonitrile and 1.5 mL of dimethyl sulfoxide, and ultrasonicate for 1 h. Seal the hydrothermal autoclave and place it in the hydrothermal autoclave. Seal the hydrothermal autoclave, and then heat the hydrothermal autoclave to 180 °C at a heating rate of 10 °C / min for 24 h. After the reaction is cooled, wash the brown precipitate with deionized water, acetonitrile, and ethanol. After washing, dry it in a vacuum oven at 60 °C for 24 h to obtain a phosphazene polymer, which is recorded as CT. (6) 0.6 mg of phosphazene polymer was mixed with 0.3 mg of copper and phosphorus co-doped g-C3N4 and mechanically ground for 30 min to obtain the phosphazene polymer / copper and phosphorus co-doped g-C3N4 heterojunction photocatalytic material, which was recorded as CT / CuPCN.

[0020] Example 3 A phosphazene polymer / copper and phosphorus co-doped g-C3N4 heterojunction photocatalytic material is prepared by the following method: (1) Weigh 5 g of melamine, heat it to 500°C at a heating rate of 10°C / min under a nitrogen atmosphere, and then calcine it for 4 h to obtain g-C3N4; (2) 3.06 g CuCl2·H2O and 100 mL methanol were weighed and placed in a clean 250 mL round-bottom flask. Ultrasonication was performed for 1 h to prepare a uniform solution. Then, 2 g g-C3N4 was slowly added under stirring to prevent agglomeration. The mixture was refluxed at 65 °C for 3 h, cooled, and the solid precipitate was collected and dried in a vacuum oven at 70 °C for 24 h. Then, the precipitate was heated to 520 °C in a nitrogen atmosphere at a heating rate of 10 °C / min and calcined for 4 h to obtain Cu-doped g-C3N4, which was recorded as CuCN. (3) Weigh 2.52 g of sodium phosphite and 100 mL of methanol, put them into a clean 250 mL round-bottom flask, and ultrasonicate for 1 h to prepare a uniform solution. Then, slowly add 2 g of g-C3N4 under stirring to prevent agglomeration. Then, reflux the mixture at 65 °C for 3 h, cool it, collect the solid precipitate, and dry it in a vacuum oven at 70 °C for 24 h. Then, heat the precipitate to 520 °C in a nitrogen atmosphere at a heating rate of 10 °C / min and calcine it for 4 h to obtain P-doped g-C3N4, which is denoted as PCN. (4) 0.4 g Cu-doped g-C3N4 and 0.5 mg P-doped g-C3N4 were mixed and mechanically ground for 30 min. The mixture was then placed in a nitrogen atmosphere, heated to 300 °C at a rate of 10 °C / min and calcined for 2 h. After naturally cooling to room temperature, the product was washed with methanol three times and then dried at 80 °C in vacuum for 24 h to obtain copper and phosphorus co-doped g-C3N4, recorded as CuPCN. (5) Weigh 0.35 g of hexachlorocyclotriphosphazene and 0.53 g of trithiocyanate into a 50 mL hydrothermal autoclave, add 30 mL of acetonitrile and 1.5 mL of dimethyl sulfoxide, and ultrasonicate for 1 h. Seal the hydrothermal autoclave and place it in the hydrothermal autoclave. Seal the hydrothermal autoclave, and then heat the hydrothermal autoclave to 180 °C at a heating rate of 10 °C / min for 24 h. After the reaction is cooled, wash the brown precipitate with deionized water, acetonitrile, and ethanol. After washing, dry it in a vacuum oven at 60 °C for 24 h to obtain a phosphazene polymer, which is recorded as CT. (6) 0.8 mg of phosphazene polymer was mixed with 0.3 mg of copper and phosphorus co-doped g-C3N4, and mechanically ground for 30 min to obtain a phosphazene polymer / copper and phosphorus co-doped g-C3N4 heterojunction photocatalytic material, which was recorded as CT / CuPCN. A phosphazene polymer / copper-doped g-C3N4 heterojunction photocatalytic material is prepared by the following method: (1) Weigh 5 g of melamine, heat it to 500 °C at a heating rate of 10 °C / min under a nitrogen atmosphere, and then calcine it for 4 h to obtain g-C3N4; (2) Weigh 2.6 g CuCl2·H2O and 100 mL methanol, put them into a clean 250 mL round-bottom flask, and ultrasonicate for 1 h to prepare a uniform solution. Then, 2 g g-C3N4 was slowly added under stirring to prevent agglomeration. The mixture was refluxed at 65 °C for 3 h, cooled, and the solid precipitate was collected and dried in a vacuum oven at 70 °C for 24 h. Then, the precipitate was heated to 520 °C in a nitrogen atmosphere at a heating rate of 10 °C / min and calcined for 4 h to obtain Cu-doped g-C3N4, denoted as CuCN. (4) Weigh 0.35 g of hexachlorocyclotriphosphazene and 0.53 g of trithiocyanate into a 50 mL hydrothermal autoclave, add 28 mL of acetonitrile and 1.5 mL of dimethyl sulfoxide, and ultrasonicate for 1 h. Seal the hydrothermal autoclave and place it in the hydrothermal autoclave. Seal the hydrothermal autoclave, and then heat the hydrothermal autoclave to 180 °C at a heating rate of 10 °C / min for 24 h. After the reaction is cooled, wash the brown precipitate with deionized water, acetonitrile, and ethanol. After washing, dry it in a vacuum oven at 60 °C for 24 h to obtain a phosphazene polymer, which is recorded as CT. (5) 0.7 mg of phosphazene polymer was mixed with 0.3 mg of copper-doped g-C3N4 and mechanically ground for 30 min to obtain the phosphazene polymer / copper-doped g-C3N4 heterojunction photocatalytic material, which was recorded as CT / CuCN.

[0021] Comparative Example 2 A phosphazene polymer / phosphorus-doped g-C3N4 heterojunction photocatalytic material is prepared by the following method: (1) Weigh 5 g of melamine, heat it to 500 °C at a heating rate of 10 °C / min under a nitrogen atmosphere, and then calcine it for 4 h to obtain g-C3N4; (2) Weigh 1.32 g of sodium hypophosphite and 100 mL of methanol, put them into a clean 250 mL round-bottom flask, and ultrasonicate for 1 h to prepare a uniform solution. Then, 3 g of g-C3N4 was slowly added under stirring to prevent agglomeration. The mixture was refluxed at 65 °C for 3 h, cooled, and the solid precipitate was collected and dried in a vacuum oven at 70 °C for 24 h. Then, the precipitate was heated to 520 °C in a nitrogen atmosphere at a heating rate of 10 °C / min and calcined for 4 h to obtain P-doped g-C3N4, denoted as PCN. (3) Weigh 0.35 g of hexachlorocyclotriphosphazene and 0.53 g of trithiocyanate into a 50 mL hydrothermal autoclave, add 28 mL of acetonitrile and 1.5 mL of dimethyl sulfoxide, and ultrasonicate for 1 h. Seal the hydrothermal autoclave and place it in the hydrothermal autoclave. Seal the hydrothermal autoclave, and then heat the hydrothermal autoclave to 180 °C at a heating rate of 10 °C / min for 24 h. After the reaction is cooled, wash the brown precipitate with deionized water, acetonitrile, and ethanol. After washing, dry it in a vacuum oven at 60 °C for 24 h to obtain a phosphazene polymer, which is recorded as CT. (4) 0.7 mg of phosphazene polymer was mixed with 0.3 mg of phosphorus-doped g-C3N4 and mechanically ground for 30 min to obtain the phosphazene polymer / phosphorus-doped g-C3N4 heterojunction photocatalytic material, which was recorded as CT / PCN.

[0022] Performance Testing The phosphazene polymer / copper and phosphorus co-doped g-C3N4 heterojunction photocatalytic material CT / CuPCN obtained in Example 1 of the present invention, Comparative Example 1, Comparative Example 2, g-C3N4 obtained in step (1) of Example 1, and the phosphazene polymer CT obtained in step (5) of Example 1 were used as test materials to test the XRD spectra of different materials. The specific results are shown in Figure 1 .like Figure 1 As shown, it can be seen that the prepared CT / CuPCN sample exhibits a weaker diffraction peak, which is consistent with the diffraction peaks of the CT and CuPCN samples, and no impurity peaks appear, proving that the CT / CuPCN sample is preliminarily synthesized.

[0023] The phosphazene polymer / copper and phosphorus co-doped g-C3N4 heterojunction photocatalytic material CT / CuPCN obtained in Example 1 of the present invention was subjected to TEM morphology test. Figure 2 .from Figure 2 As can be seen from the information in the figure, the CT / CuPCN sample shows a structure with multiple thin layers covering each other. This structure has large and strong interfacial contacts, excellent visible light absorption ability, porous structure, spatially separated redox sites, and rapid separation of photoinduced charge carriers.

[0024] The phosphazene polymer / copper and phosphorus co-doped g-C3N4 heterojunction photocatalytic material CT / CuPCN obtained in Example 1 of the present invention, Comparative Example 1, Comparative Example 2, g-C3N4 obtained in step (1) of Example 1, and the phosphazene polymer CT obtained in step (5) of Example 1 were used as test materials to test the photocatalytic CO2 reduction performance of different materials. The specific results are shown in Figure 3 As shown. Figure 3It can be seen that the CT / CuPCN sample prepared in Example 1 of the present invention has a yield of 1520.8 μmol / g for the production of CH4 by catalytic reduction of CO2 under visible light irradiation, showing excellent photocatalytic activity. Its photocatalytic reduction of CO2 to produce CH4 yield is significantly greater than that of Comparative Example 1 and Comparative Example 2, and is also significantly greater than the sum of the yields of Comparative Example 1 and Comparative Example 2, which indicates that the heterojunction photocatalytic material formed by the combined use of copper and phosphorus co-doped g-C3N4 and phosphazene polymer has a significant synergistic effect in the process of catalytic reduction of CO2 to produce CH4.

[0025] The present invention also performs impedance tests on Example 1, Comparative Example 1, Comparative Example 2, g-C3N4 obtained in step (1) of Example 1, and phosphazene polymer CT material obtained in step (5) of Example 1. Figure 4 .like Figure 4 As shown, the phosphazene polymer / copper and phosphorus co-doped g-C3N4 heterojunction photocatalytic material CT / CuPCN sample prepared in Example 1 has the smallest Enquist radius, which indicates that the charge transfer barrier in the heterostructure is small, allowing rapid transport and separation of photoinduced charges, and thus has good photocatalytic activity.

[0026] It should be noted that the above embodiments are only partial embodiments of the preferred methods of implementing the present invention, rather than all embodiments. Obviously, based on the above embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

Claims

1. A method for preparing a phosphazene polymer / copper and phosphorus co-doped g-C3N4 heterojunction photocatalytic material, characterized in that: It includes the following steps: (1) Melamine was calcined at high temperature for 4 h under nitrogen atmosphere to obtain g-C3N4; (2) preparing a copper salt methanol solution, slowly adding the g-C3N4 obtained in step (1) thereto while stirring, stirring and mixing evenly, heating to 65°C for reflux reaction for 3-4 hours, collecting the solid precipitate after the reaction, vacuum drying it, transferring it to a tube furnace, and calcining it at high temperature for 4 hours under a nitrogen atmosphere to obtain Cu-doped g-C3N4; (3) preparing a methanol solution of phosphate, slowly adding the g-C3N4 obtained in step (1) thereto while stirring, stirring and mixing evenly, heating to 65°C for reflux reaction for 3-4 hours, collecting the solid precipitate after the reaction is completed, vacuum drying it, transferring it to a tube furnace, and calcining it at high temperature for 4 hours under a nitrogen atmosphere to obtain P-doped g-C3N4; (4) The Cu-doped g-C3N4 and P-doped g-C3N4 obtained in the above step were mixed according to the mass ratio and mechanically ground for 30 min. The mixture was then placed in a nitrogen atmosphere and calcined at high temperature for 2 h. After naturally cooling to room temperature, the product was washed with methanol three times and then vacuum dried at 80 °C for 24 h to obtain copper and phosphorus co-doped g-C3N4. (5) Hexachlorocyclotriphosphazene, trithiocyanate, acetonitrile and dimethyl sulfoxide were added into a hydrothermal reactor in proportion, and ultrasonic treatment was first performed for 1 hour, and then heated to 180°C and kept warm for reaction for 24-28 hours. After the reaction was completed, the product was naturally cooled and washed with deionized water, acetonitrile and ethanol in sequence. After washing, it was vacuum dried at 60°C for 24 hours to obtain a phosphazene polymer; (6) The phosphazene polymer obtained in step (5) and the copper and phosphorus co-doped g-C3N4 obtained in step (4) are mixed in a mass ratio, and mechanically ground for 30 minutes to obtain the phosphazene polymer / copper and phosphorus co-doped g-C3N4 heterojunction photocatalytic material.

2. The method for preparing the phosphazene polymer / copper and phosphorus co-doped g-C3N4 heterojunction photocatalytic material according to claim 1, characterized in that: The specific method of high temperature calcination in step (1) is: heating to 500° C. at a rate of 10° C. / min and then calcining for 4 h.

3. The method for preparing the phosphazene polymer / copper and phosphorus co-doped g-C3N4 heterojunction photocatalytic material according to claim 1, characterized in that: In the step (2), the concentration of the copper salt methanol solution is 0.1-0.2 mol / L; the usage ratio of the copper salt methanol solution to g-C3N4 is 100 ml: 2-3 g; and the copper salt is copper chloride or copper nitrate.

4. The method for preparing the phosphazene polymer / copper and phosphorus co-doped g-C3N4 heterojunction photocatalytic material according to claim 1, characterized in that: The concentration of the methanol solution of phosphate in step (3) is 0.1-0.2 mol / L; the usage ratio of the methanol solution of phosphate to g-C3N4 is 100 ml: 2-3 g; the phosphate is sodium hypophosphite or sodium phosphite.

5. The method for preparing the phosphazene polymer / copper and phosphorus co-doped g-C3N4 heterojunction photocatalytic material according to claim 1, characterized in that: The specific method of high temperature calcination in step (2) and step (3) is: heating to 520° C. at a rate of 10° C. / min and then calcining for 4 hours.

6. The method for preparing the phosphazene polymer / copper and phosphorus co-doped g-C3N4 heterojunction photocatalytic material according to claim 1, characterized in that: In the step (4), the mass ratio of Cu-doped g-C3N4 to P-doped g-C3N4 is 700-800:1; the specific method of high-temperature calcination is: heating to 300°C at a rate of 10°C / min and then calcining for 2h.

7. The method for preparing the phosphazene polymer / copper and phosphorus co-doped g-C3N4 heterojunction photocatalytic material according to claim 1, characterized in that: In the step (5), the usage ratio of hexachlorocyclotriphosphazene, trithiocyanuric acid, acetonitrile and dimethyl sulfoxide is 1 mol: 3 mol: 25-30 L: 1.5 L.

8. The method for preparing the phosphazene polymer / copper and phosphorus co-doped g-C3N4 heterojunction photocatalytic material according to claim 1, characterized in that: In the step (6), the mass ratio of the phosphazene polymer to the copper and phosphorus co-doped g-C3N4 is 6-8:

3.

9. A phosphazene polymer / copper and phosphorus co-doped g-C3N4 heterojunction photocatalytic material, characterized in that: The invention discloses a novel nanostructured carbon foam prepared by the preparation method described in any one of claims 1 to 8.

10. Use of the phosphazene polymer / copper and phosphorus co-doped g-C3N4 heterojunction photocatalytic material according to claim 9 in CO2 reduction to produce CH4.

Citation Information

Patent Citations

  • Nanocopper / cyclic polyacrylonitrile composite photocatalyst and preparation method thereof

    CN107469864A

  • P and S codoped carbon nitride homotype heterojunction composite photocatalyst

    CN110876953A

  • AG3vo4 modified phosphorus and sulphur co-doped graphitic carbon nitride as high-dispersed photocatalyst for phenol mineralization and e. coli disinfection

    IN201811033392A